2013
DOI: 10.2169/internalmedicine.52.0731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rosuvastatin vs. Simvastatin/ezetimibe on Arterial Wall Stiffness in Patients with Coronary Artery Disease

Abstract: Objective Statins prevent cardiovascular events in patients with coronary artery disease (CAD). However, there is little information regarding the vascular effects of statins on arterial wall stiffness in CAD patients. Methods A total of 36 patients were randomly assigned to receive rosuvastatin (10 mg per day) or simvastatin/ezetimibe (10/10 mg per day) for eight weeks. The aim of the present study was to determine the effects of rosuvastatin or simvastatin/ezetimibe on arterial wall stiffness measured accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…Direct Treatment of PWV A number of short-term randomised controlled trials investigating the blockade/ inhibition of renin [71], angiotensin converting enzyme/ angiotensin AT1 receptor blockers [72][73][74][75][76][77][78][79][80], endothelin [81], aldosterone [82,83], phosphodiesterase V [84,85], HMGcoA reductase [86][87][88][89][90][91][92] and xanthine oxidase [93] have been shown to reduce aortic PWV. An important randomised trial in patients with early renal impairment showed both PWV and left ventricular mass reduction over 1 year on just 25 mg spironolactone versus placebo, which the authors claimed was independent of BP [94].…”
Section: Origins Of Arterial Stiffness and Nurture Versus Nature?mentioning
confidence: 99%
“…Direct Treatment of PWV A number of short-term randomised controlled trials investigating the blockade/ inhibition of renin [71], angiotensin converting enzyme/ angiotensin AT1 receptor blockers [72][73][74][75][76][77][78][79][80], endothelin [81], aldosterone [82,83], phosphodiesterase V [84,85], HMGcoA reductase [86][87][88][89][90][91][92] and xanthine oxidase [93] have been shown to reduce aortic PWV. An important randomised trial in patients with early renal impairment showed both PWV and left ventricular mass reduction over 1 year on just 25 mg spironolactone versus placebo, which the authors claimed was independent of BP [94].…”
Section: Origins Of Arterial Stiffness and Nurture Versus Nature?mentioning
confidence: 99%
“…For example, in one controlled trial, 36 participants with coronary artery disease were randomized to orally ingest either rosuvastatin (10 mg daily) or simvastatin/ezetimibe (10/10 mg/day) for 8 weeks. In this trial, the value of the baPWV did not change in the simvastatin/ezetimibe group, while it improved significantly in the rosuvastatin-treated group when compared with baseline values (from 1772 ± 430 cm/s to 1603 ± 398 cm/s) and baPWV values for the simvastatin/ezetimibe group [97]. In another clinical trial conducted by Ilyukhin et al, 38 ischemic heart disease patients were administered either 10 mg/day atorvastatin or 20 mg/day simvastatin, for 6 months.…”
Section: Comparison Of Different Statinsmentioning
confidence: 56%
“…On the contrary, 20-week treatment with statins (rosuvastatin or atorvastatin) combined with regular exercise significantly improved exercise capacity and brachial artery PWV, but had no effect on blood pressure [ 76 ]. In patients with coronary artery disease compared with simvastatin/ezetimibe, rosuvastatin was found to more effectively improve arterial wall stiffness [ 77 ]. Although the beneficial effect of statin on stiffness parameters in various patient populations are well established, to date, their effects on stiffness parameters in FH patients has not been investigated.…”
Section: Effect Of Traditional Oral Lipid-lowering Treatment On Arter...mentioning
confidence: 99%